Preparation method of high-purity anhydrous indium sulfate

By using multiple evaporation concentration and thermal decomposition methods in the preparation process of anhydrous indium sulfate, the problem of indium sulfate products being prone to blackening and yellowing is solved, the density and purity of the products are improved, and the production cost is reduced.

CN119551710APending Publication Date: 2025-03-04XIANDAO THIN FILM MATERIALS GUANGDONG CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411568108.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

In the prior art, anhydrous indium sulfate products are prone to blackening and yellowing, which affects product yield and cost.

Method used

By placing the indium strips in a sulfuric acid solution and heating the reaction, standing, filtering, evaporating and concentrating until the pH is 2-3, evaporating and crystallization are concentrated, washed, dried, and finally thermal decomposition is carried out to obtain high-purity anhydrous indium sulfate.

Benefits of technology

Effectively remove the problems of blackening and yellowing in anhydrous indium sulfate products, improve particle density, reduce particle pore ratio, reduce production costs, and simple operation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119551710A_ABST
    Figure CN119551710A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of high-purity anhydrous indium sulfate, which belongs to the technical field of chemistry and chemical engineering, and creatively comprises the steps of acid leaching of an indium strip, multiple times of evaporation and concentration until the pH value is 2-3, evaporation, crystallization and concentration, washing, drying and thermal decomposition, so that the problems of blackening and yellowing in an anhydrous indium sulfate product are effectively solved, the particle compactness is improved, and the yield is improved. The method provided by the invention has the advantages of low production cost, simplicity in operation and wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of chemistry and chemical engineering, and in particular to a method for preparing high-purity anhydrous indium sulfate. Background Art

[0002] Indium sulfate, with a relative molecular mass of 517.82, is a white inorganic compound crystal that is relatively stable at room temperature and pressure. It is easy to form sulfate ions and indium ions in aqueous solution, and the solution is acidic. The main production method of indium sulfate is diaphragm electrolysis of indium sulfate solution-evaporation crystallization-vacuum crystallization-vacuum heating to obtain indium sulfate powder, which is often used as a raw material in semiconductor, electroplating, ceramic, and optoelectronic industries. The purity of indium sulfate is one of the important factors affecting product performance. The conventional raw materials for preparing indium sulfate are crude indium and indium oxide. There are problems such as low purity of indium sulfate products, easy yellowing and blackening, and easy generation of suspended matter when dissolved in water, which seriously affects the product yield, which is only 50-75%, and the production cost is relatively high.

[0003] CN118419968A discloses a method for preparing anhydrous indium sulfate, which comprises mixing sulfuric acid, indium oxide and hydrogen peroxide, separating the solid and the liquid, concentrating and crystallizing the separated liquid, and preparing crude indium sulfate. The crude indium sulfate is then dissolved in deionized water, evaporated and crystallized, and anhydrous indium sulfate is obtained. Although anhydrous indium sulfate with high purity is prepared, the prepared indium sulfate has the problem of being easily yellowed and blackened.

[0004] CN103880065A discloses a method and device for preparing indium sulfate. The method only requires that the filtrate obtained by heating the indium raw material and then filtering it is dripped onto a quartz plate with running water on the surface, which can be quickly cooled to form indium with a high specific surface area. The indium sulfate is then obtained by heating, filtering, evaporating and roasting to form a mixed solution with water and concentrated sulfuric acid. The process is simple and stable, effectively reduces contamination by other impurities, ensures the preparation of indium with a high specific surface area, and reduces the loss of indium in the entire process. However, the method requires the use of a special preparation device, and the method still cannot solve the problem that indium sulfate is prone to yellowing and blackening.

[0005] In view of this, this application is filed. Summary of the invention

[0006] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a method for preparing high-purity anhydrous indium sulfate, which effectively solves the problem of blackening and yellowing in anhydrous indium sulfate products.

[0007] To achieve the above object, the technical solution adopted by the present invention is:

[0008] A method for preparing high-purity anhydrous indium sulfate comprises the following steps:

[0009] (1) placing an indium bar in a sulfuric acid solution, heating for reaction, standing, and filtering to obtain a first solution;

[0010] (2) evaporating and concentrating the first solution to 60% to 70% of the original volume to obtain a second solution;

[0011] (3) adding water to the second solution and evaporating and concentrating the solution to 60-70% of the original volume to obtain a third solution;

[0012] (4) Repeat step (3) until the pH of the resulting solution is 2 to 3;

[0013] (5) filtering the solution of step (4), evaporating, concentrating and crystallizing to obtain high-purity indium sulfate nonahydrate;

[0014] (6) Wash the high-purity indium sulfate nonahydrate with a detergent 2 to 3 times and dry it to obtain high-purity xH 2 O.In 2 (SO 4 ) 3 Crystals;

[0015] (7) High purity xH 2 O.In 2 (SO 4 ) 3 The crystals are placed in a quartz boat, nitrogen is introduced, and thermal decomposition is performed to obtain high-purity anhydrous indium sulfate.

[0016] The invention creatively performs acid leaching of indium strips, multiple evaporation concentration to a pH value of 2-3, evaporation crystallization concentration, washing, drying, and thermal decomposition, thereby effectively removing the blackening and yellowing problems in anhydrous indium sulfate products, improving particle density, and reducing particle porosity. The method of the invention has low production cost, simple operation, and broad application prospects.

[0017] As a preferred embodiment of the present invention, the purity of the indium bar is ≥3N.

[0018] As a preferred embodiment of the present invention, the concentration of the sulfuric acid solution is 10 to 200 g / L.

[0019] As a preferred embodiment of the present invention, the solid-to-liquid ratio of the indium rod to the sulfuric acid solution is 1 g: (4-6) mL.

[0020] As a preferred embodiment of the present invention, the temperature of the heating reaction is 75-85°C.

[0021] As a preferred embodiment of the present invention, the temperature of evaporation concentration in step (2) and step (3) is 90-100°C.

[0022] As a preferred embodiment of the present invention, the temperature of the evaporation concentration crystallization is 90-100° C. and the time is 6-12 hours.

[0023] As a preferred embodiment of the present invention, the detergent includes at least one of anhydrous acetic acid, anhydrous formic acid, and hydrogen cyanide.

[0024] As a preferred embodiment of the present invention, the nitrogen introduction amount is 10 to 15 L / min. By controlling the nitrogen introduction amount within this range, the present invention effectively removes bound water, reduces the hardness of the product, and prevents the formation of black, insoluble sulfate particles.

[0025] As a preferred embodiment of the present invention, the thermal decomposition temperature is 300-500°C, and the thermal decomposition time is 10-15h. Controlling the thermal decomposition temperature within this range can effectively remove sulfate ions, avoid blackening of the product, avoid generating indium oxide, improve product purity, and avoid yellowing and hardening of the product surface.

[0026] The beneficial effects of the present invention are as follows: the present invention creatively performs acid leaching of indium strips, multiple evaporation concentrations to a pH value of 2 to 3, evaporation crystallization concentration, washing, drying, and thermal decomposition, thereby effectively removing the blackening and yellowing problems in anhydrous indium sulfate products, improving particle density, and reducing particle porosity. The method described in the present invention has low production cost, simple operation, and broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The high-purity anhydrous indium sulfate prepared in Example 1.

[0028] Figure 2 This is the high-purity anhydrous indium sulfate prepared in Comparative Example 2. DETAILED DESCRIPTION

[0029] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.

[0030] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0031] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0032] In the present application, there is no particular limitation on the specific dispersion and stirring treatment methods.

[0033] Unless otherwise specified, the components, raw materials or instruments used in the embodiments and comparative examples of the present invention are all commercially available raw materials or instruments, and the components and raw materials used in each parallel experiment are all of the same kind.

[0034] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of the present invention, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0035] The following examples are provided to facilitate understanding of the present invention. These examples are not provided to limit the scope of the claims.

[0036] Example 1

[0037] A method for preparing high-purity anhydrous indium sulfate comprises the following steps:

[0038] (1) placing an indium bar with a purity of 4N in a 120 g / L sulfuric acid solution, heating to 80° C. to react until the indium bar is completely dissolved, standing for 4 hours, filtering, and obtaining a first solution; the solid-liquid ratio of the indium bar to the sulfuric acid solution is 1 g:5 mL.

[0039] Wherein, the 4N indium bar: the total impurity content of the purity is less than 100ppm, the purity of the indium content is greater than 99.99%, and Cd <10ppm, Sn <10ppm, Bi <10ppm, Tl <10ppm, Zn <10ppm, Pb <10ppm, Ni <10ppm, and the remaining impurities are less than 5ppm;

[0040] (2) adding the first solution into an evaporator and evaporating and concentrating the solution to 1 / 3 of the original volume at 95° C. to obtain a second solution;

[0041] (3) adding water to the second solution, and then adding the solution to an evaporator, evaporating and concentrating the solution to 1 / 3 of the original volume to obtain a third solution;

[0042] (4) Repeat step (3) until the pH of the resulting solution is between 2 and 3;

[0043] (5) filtering the solution of step (4), evaporating, concentrating and crystallizing at 95° C. for 10 h to obtain high-purity indium sulfate nonahydrate;

[0044] (6) Wash the high-purity indium sulfate nonahydrate with anhydrous acetic acid three times and dry at 95°C for 24 hours to obtain high-purity xH 2 O.In 2 (SO 4 ) 3 Crystals;

[0045] (7) High purity xH 2 O.In 2 (SO 4 ) 3 The crystals were placed in a quartz boat, and then placed in a pyrolysis furnace, nitrogen was introduced at a rate of 12 L / min, and thermal decomposition was performed at 400°C for 12 hours to obtain high-purity anhydrous indium sulfate.

[0046] The actual picture of the high-purity anhydrous indium sulfate prepared in this embodiment is as follows: Figure 1 As shown, the yellowing and blackening problems of the product can be completely eliminated, the porosity ratio is less than 0.6, the particles are uniform and dense, the black spots and yellowing substances almost disappear, and the brittleness is good.

[0047] Example 2

[0048] A method for preparing high-purity anhydrous indium sulfate comprises the following steps:

[0049] (1) placing an indium bar with a purity of 4N in a 120 g / L sulfuric acid solution, heating to 80° C. to react until the indium bar is completely dissolved, standing for 4 hours, filtering, and obtaining a first solution; the solid-liquid ratio of the indium bar to the sulfuric acid solution is 1 g:5 mL.

[0050] Wherein, the 4N indium bar: the total impurity content of the purity is less than 100ppm, the purity of the indium content is greater than 99.99%, and Cd <10ppm, Sn <10ppm, Bi <10ppm, Tl <10ppm, Zn <10ppm, Pb <10ppm, Ni <10ppm, and the remaining impurities are less than 5ppm;

[0051] (2) adding the first solution into an evaporator and evaporating and concentrating the solution to 1 / 3 of the original volume at 95° C. to obtain a second solution;

[0052] (3) adding water to the second solution, and then adding the solution to an evaporator, evaporating and concentrating the solution to 1 / 3 of the original volume to obtain a third solution;

[0053] (4) Repeat step (3) until the pH of the resulting solution is between 2 and 3;

[0054] (5) filtering the solution of step (4), evaporating, concentrating and crystallizing at 95° C. for 10 h to obtain high-purity indium sulfate nonahydrate;

[0055] (6) Wash the high-purity indium sulfate nonahydrate with anhydrous acetic acid three times and dry at 95°C for 24 hours to obtain high-purity xH 2 O.In 2 (SO 4 ) 3 Crystals;

[0056] (7) High purity xH 2 O.In 2 (SO 4 ) 3 The crystals were placed in a quartz boat, and then placed in a pyrolysis furnace, nitrogen was introduced at a rate of 15 L / min, and thermal decomposition was performed at 300° C. for 15 h to obtain high-purity anhydrous indium sulfate.

[0057] Example 3

[0058] A method for preparing high-purity anhydrous indium sulfate comprises the following steps:

[0059] (1) placing an indium bar with a purity of 4N in a 120 g / L sulfuric acid solution, heating to 80° C. to react until the indium bar is completely dissolved, standing for 4 hours, filtering, and obtaining a first solution; the solid-liquid ratio of the indium bar to the sulfuric acid solution is 1 g:5 mL.

[0060] Wherein, the 4N indium bar: the total impurity content of the purity is less than 100ppm, the purity of the indium content is greater than 99.99%, and Cd <10ppm, Sn <10ppm, Bi <10ppm, Tl <10ppm, Zn <10ppm, Pb <10ppm, Ni <10ppm, and the remaining impurities are less than 5ppm;

[0061] (2) adding the first solution into an evaporator and evaporating and concentrating the solution to 1 / 3 of the original volume at 95° C. to obtain a second solution;

[0062] (3) adding water to the second solution, and then adding the solution to an evaporator, evaporating and concentrating the solution to 1 / 3 of the original volume to obtain a third solution;

[0063] (4) Repeat step (3) until the pH of the resulting solution is between 2 and 3;

[0064] (5) filtering the solution of step (4), evaporating, concentrating and crystallizing at 95° C. for 10 h to obtain high-purity indium sulfate nonahydrate;

[0065] (6) Wash the high-purity indium sulfate nonahydrate with anhydrous acetic acid three times and dry at 95°C for 24 hours to obtain high-purity xH 2 O.In 2 (SO 4 ) 3 Crystals;

[0066] (7) High purity xH 2 O.In 2 (SO 4 ) 3 The crystals were placed in a quartz boat, and then placed in a pyrolysis furnace, nitrogen was introduced at a rate of 10 L / min, and thermal decomposition was performed at 500° C. for 10 h to obtain high-purity anhydrous indium sulfate.

[0067] Example 4

[0068] A method for preparing high-purity anhydrous indium sulfate comprises the following steps:

[0069] (1) placing an indium bar with a purity of 4N in a 120 g / L sulfuric acid solution, heating to 80° C. to react until the indium bar is completely dissolved, standing for 4 hours, filtering, and obtaining a first solution; the solid-liquid ratio of the indium bar to the sulfuric acid solution is 1 g:5 mL.

[0070] Wherein, the 4N indium bar: the total impurity content of the purity is less than 100ppm, the purity of the indium content is greater than 99.99%, and Cd <10ppm, Sn <10ppm, Bi <10ppm, Tl <10ppm, Zn <10ppm, Pb <10ppm, Ni <10ppm, and the remaining impurities are less than 5ppm;

[0071] (2) adding the first solution into an evaporator and evaporating and concentrating the solution to 1 / 3 of the original volume at 95° C. to obtain a second solution;

[0072] (3) adding water to the second solution, and then adding the solution to an evaporator, evaporating and concentrating the solution to 1 / 3 of the original volume to obtain a third solution;

[0073] (4) Repeat step (3) until the pH of the resulting solution is between 2 and 3;

[0074] (5) filtering the solution of step (4), evaporating, concentrating and crystallizing at 95° C. for 10 h to obtain high-purity indium sulfate nonahydrate;

[0075] (6) Wash the high-purity indium sulfate nonahydrate with anhydrous formic acid three times and dry at 95°C for 24 hours to obtain high-purity xH 2 O.In 2 (SO 4 ) 3 Crystals;

[0076] (7) High purity xH2 O.In 2 (SO 4 ) 3 The crystals were placed in a quartz boat, and then placed in a pyrolysis furnace, nitrogen was introduced at a rate of 12 L / min, and thermal decomposition was performed at 400°C for 12 hours to obtain high-purity anhydrous indium sulfate.

[0077] Example 5

[0078] A method for preparing high-purity anhydrous indium sulfate comprises the following steps:

[0079] (1) placing an indium bar with a purity of 4N in a 120 g / L sulfuric acid solution, heating to 80° C. to react until the indium bar is completely dissolved, standing for 4 hours, filtering, and obtaining a first solution; the solid-liquid ratio of the indium bar to the sulfuric acid solution is 1 g:5 mL.

[0080] Wherein, the 4N indium bar: the total impurity content of the purity is less than 100ppm, the purity of the indium content is greater than 99.99%, and Cd <10ppm, Sn <10ppm, Bi <10ppm, Tl <10ppm, Zn <10ppm, Pb <10ppm, Ni <10ppm, and the remaining impurities are less than 5ppm;

[0081] (2) adding the first solution into an evaporator and evaporating and concentrating the solution to 1 / 3 of the original volume at 95° C. to obtain a second solution;

[0082] (3) adding water to the second solution, and then adding the solution to an evaporator, evaporating and concentrating the solution to 1 / 3 of the original volume to obtain a third solution;

[0083] (4) Repeat step (3) until the pH of the resulting solution is between 2 and 3;

[0084] (5) filtering the solution of step (4), evaporating, concentrating and crystallizing at 95° C. for 10 h to obtain high-purity indium sulfate nonahydrate;

[0085] (6) Wash the high-purity indium sulfate nonahydrate with hydrogen cyanide three times and dry at 95°C for 24 hours to obtain high-purity xH 2 O.In 2 (SO 4 ) 3 Crystals;

[0086] (7) High purity xH 2 O.In 2 (SO 4 ) 3 The crystals were placed in a quartz boat, and then placed in a pyrolysis furnace, nitrogen was introduced at a rate of 12 L / min, and thermal decomposition was performed at 400°C for 12 hours to obtain high-purity anhydrous indium sulfate.

[0087] Comparative Example 1

[0088] A method for preparing high-purity anhydrous indium sulfate comprises the following steps:

[0089] (1) placing an indium bar with a purity of 4N in a 120 g / L sulfuric acid solution, heating to 80° C. to react until the indium bar is completely dissolved, standing for 4 hours, filtering, and obtaining a first solution; the solid-liquid ratio of the indium bar to the sulfuric acid solution is 1 g:5 mL.

[0090] Wherein, the 4N indium bar: the total impurity content of the purity is less than 100ppm, the purity of the indium content is greater than 99.99%, and Cd <10ppm, Sn <10ppm, Bi <10ppm, Tl <10ppm, Zn <10ppm, Pb <10ppm, Ni <10ppm, and the remaining impurities are less than 5ppm;

[0091] (2) adding the first solution into an evaporator and evaporating and concentrating the solution to 1 / 3 of the original volume at 95° C. to obtain a second solution;

[0092] (3) adding water to the second solution, and then adding the solution to an evaporator, evaporating and concentrating the solution to 1 / 3 of the original volume to obtain a third solution;

[0093] (4) filtering the solution of step (3), evaporating, concentrating and crystallizing at 95° C. for 10 h to obtain high-purity indium sulfate nonahydrate;

[0094] (5) Wash the high-purity indium sulfate nonahydrate with anhydrous acetic acid three times and dry at 95°C for 24 hours to obtain high-purity xH 2 O.In 2 (SO 4 ) 3 Crystals;

[0095] (6) High purity xH 2 O.In 2 (SO 4 ) 3 The crystals were placed in a quartz boat, and then placed in a pyrolysis furnace, nitrogen was introduced at a rate of 12 L / min, and thermal decomposition was performed at 400°C for 12 hours to obtain high-purity anhydrous indium sulfate.

[0096] Comparative Example 2

[0097] A method for preparing high-purity anhydrous indium sulfate comprises the following steps:

[0098] (1) placing an indium bar with a purity of 4N in a 120 g / L sulfuric acid solution, heating to 80° C. to react until the indium bar is completely dissolved, standing for 4 hours, filtering, and obtaining a first solution; the solid-liquid ratio of the indium bar to the sulfuric acid solution is 1 g:5 mL.

[0099] Wherein, the 4N indium bar: the total impurity content of the purity is less than 100ppm, the purity of the indium content is greater than 99.99%, and Cd <10ppm, Sn <10ppm, Bi <10ppm, Tl <10ppm, Zn <10ppm, Pb <10ppm, Ni <10ppm, and the remaining impurities are less than 5ppm;

[0100] (2) adding the first solution into an evaporator and evaporating and concentrating the solution to 1 / 3 of the original volume at 95° C. to obtain a second solution;

[0101] (3) adding water to the second solution, and then adding the solution to an evaporator, evaporating and concentrating the solution to 1 / 3 of the original volume to obtain a third solution;

[0102] (4) Repeat step (3) until the pH of the resulting solution is between 2 and 3;

[0103] (5) filtering the solution of step (4), evaporating, concentrating and crystallizing at 95° C. for 10 h to obtain high-purity indium sulfate nonahydrate;

[0104] (6) Wash the high-purity indium sulfate nonahydrate with water three times and dry it at 95°C for 24 hours to obtain high-purity xH 2 O.In 2 (SO 4 ) 3 Crystals;

[0105] (7) High purity xH 2 O.In 2 (SO 4 ) 3 The crystals were placed in a quartz boat, and then placed in a pyrolysis furnace, nitrogen was introduced at a rate of 12 L / min, and thermal decomposition was performed at 400°C for 12 hours to obtain high-purity anhydrous indium sulfate.

[0106] The actual picture of the high-purity anhydrous indium sulfate prepared in this embodiment is as follows: Figure 2 As shown, the product is relatively hard, has more black spots (occupying about 1 / 3 of the surface area on both sides of the product), a small amount of yellowing, and a porosity ratio greater than 1, and the particles are coarse and uneven.

[0107] Comparative Example 3

[0108] A method for preparing high-purity anhydrous indium sulfate comprises the following steps:

[0109] (1) placing an indium bar with a purity of 4N in a 120 g / L sulfuric acid solution, heating to 80° C. to react until the indium bar is completely dissolved, standing for 4 hours, filtering, and obtaining a first solution; the solid-liquid ratio of the indium bar to the sulfuric acid solution is 1 g:5 mL.

[0110] Wherein, the 4N indium bar: the total impurity content of the purity is less than 100ppm, the purity of the indium content is greater than 99.99%, and Cd <10ppm, Sn <10ppm, Bi <10ppm, Tl <10ppm, Zn <10ppm, Pb <10ppm, Ni <10ppm, and the remaining impurities are less than 5ppm;

[0111] (2) adding the first solution into an evaporator and evaporating and concentrating the solution to 1 / 3 of the original volume at 95° C. to obtain a second solution;

[0112] (3) adding water to the second solution, and then adding the solution to an evaporator, evaporating and concentrating the solution to 1 / 3 of the original volume to obtain a third solution;

[0113] (4) Repeat step (3) until the pH of the resulting solution is between 2 and 3;

[0114] (5) filtering the solution of step (4), evaporating, concentrating and crystallizing at 95° C. for 10 h to obtain high-purity indium sulfate nonahydrate;

[0115] (6) Wash the high-purity indium sulfate nonahydrate with anhydrous ethanol three times and dry at 95°C for 24 hours to obtain high-purity xH 2 O.In 2 (SO 4 ) 3 Crystals;

[0116] (7) High purity xH 2 O.In 2 (SO 4 ) 3 The crystals were placed in a quartz boat, and then placed in a pyrolysis furnace, nitrogen was introduced at a rate of 12 L / min, and thermal decomposition was performed at 400°C for 12 hours to obtain high-purity anhydrous indium sulfate.

[0117] Comparative Example 4

[0118] A method for preparing high-purity anhydrous indium sulfate comprises the following steps:

[0119] (1) placing an indium bar with a purity of 4N in a 120 g / L sulfuric acid solution, heating to 80° C. to react until the indium bar is completely dissolved, standing for 4 hours, filtering, and obtaining a first solution; the solid-liquid ratio of the indium bar to the sulfuric acid solution is 1 g:5 mL.

[0120] Wherein, the 4N indium bar: the total impurity content of the purity is less than 100ppm, the purity of the indium content is greater than 99.99%, and Cd <10ppm, Sn <10ppm, Bi <10ppm, Tl <10ppm, Zn <10ppm, Pb <10ppm, Ni <10ppm, and the remaining impurities are less than 5ppm;

[0121] (2) adding the first solution into an evaporator and evaporating and concentrating the solution to 1 / 3 of the original volume at 95° C. to obtain a second solution;

[0122] (3) adding water to the second solution, and then adding the solution to an evaporator, evaporating and concentrating the solution to 1 / 3 of the original volume to obtain a third solution;

[0123] (4) Repeat step (3) until the pH of the resulting solution is between 2 and 3;

[0124] (5) filtering the solution of step (4), evaporating, concentrating and crystallizing at 95° C. for 10 h to obtain high-purity indium sulfate nonahydrate;

[0125] (6) Wash the high-purity indium sulfate nonahydrate with anhydrous acetic acid three times and dry at 95°C for 24 hours to obtain high-purity xH 2 O.In 2 (SO 4 ) 3 Crystals;

[0126] (7) High purity xH 2 O.In 2 (SO 4 ) 3 The crystals were placed in a quartz boat, and then placed in a pyrolysis furnace, nitrogen was introduced at a rate of 5 L / min, and thermal decomposition was performed at 400°C for 12 hours to obtain high-purity anhydrous indium sulfate.

[0127] Comparative Example 5

[0128] A method for preparing high-purity anhydrous indium sulfate comprises the following steps:

[0129] (1) placing an indium bar with a purity of 4N in a 120 g / L sulfuric acid solution, heating to 80° C. to react until the indium bar is completely dissolved, standing for 4 hours, filtering, and obtaining a first solution; the solid-liquid ratio of the indium bar to the sulfuric acid solution is 1 g:5 mL.

[0130] Wherein, the 4N indium bar: the total impurity content of the purity is less than 100ppm, the purity of the indium content is greater than 99.99%, and Cd <10ppm, Sn <10ppm, Bi <10ppm, Tl <10ppm, Zn <10ppm, Pb <10ppm, Ni <10ppm, and the remaining impurities are less than 5ppm;

[0131] (2) adding the first solution into an evaporator and evaporating and concentrating the solution to 1 / 3 of the original volume at 95° C. to obtain a second solution;

[0132] (3) adding water to the second solution, and then adding the solution to an evaporator, evaporating and concentrating the solution to 1 / 3 of the original volume to obtain a third solution;

[0133] (4) Repeat step (3) until the pH of the resulting solution is between 2 and 3;

[0134] (5) filtering the solution of step (4), evaporating, concentrating and crystallizing at 95° C. for 10 h to obtain high-purity indium sulfate nonahydrate;

[0135] (6) Wash the high-purity indium sulfate nonahydrate with anhydrous acetic acid three times and dry at 95°C for 24 hours to obtain high-purity xH 2 O.In 2 (SO 4 ) 3 Crystals;

[0136] (7) High purity xH 2 O.In 2 (SO 4 ) 3 The crystals were placed in a quartz boat, and then placed in a pyrolysis furnace, nitrogen was introduced at a rate of 20 L / min, and thermal decomposition was performed at 400°C for 12 hours to obtain high-purity anhydrous indium sulfate.

[0137] Test Case

[0138] The performance of the products of the embodiments and comparative examples are shown in Table 1.

[0139] Table 1

[0140]

[0141]

[0142] As can be seen from Table 1, the method described in the present invention can effectively solve the problem of blackening and yellowing in anhydrous indium sulfate products, improve particle density, and reduce particle porosity.

[0143] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A method for preparing high-purity anhydrous indium sulfate, characterized in that: The following steps are involved: (1) placing an indium bar in a sulfuric acid solution, heating for reaction, standing, and filtering to obtain a first solution; (2) evaporating and concentrating the first solution to 60% to 70% of the original volume to obtain a second solution; (3) adding water to the second solution and evaporating and concentrating the solution to 60-70% of the original volume to obtain a third solution; (4) Repeat step (3) until the pH of the resulting solution is 2 to 3; (5) filtering the solution of step (4), evaporating, concentrating and crystallizing to obtain high-purity indium sulfate nonahydrate; (6) washing the high-purity indium sulfate nonahydrate with a detergent for 2 to 3 times, and drying to obtain high-purity xH2O·In2(SO4)3 crystals; (7) High-purity xH2O·In2(SO4)3 crystals are placed in a quartz boat, nitrogen is introduced, and thermal decomposition is performed to obtain high-purity anhydrous indium sulfate.

2. The method for preparing high-purity anhydrous indium sulfate according to claim 1, characterized in that: The purity of the indium bar is ≥3N.

3. The method for preparing high-purity anhydrous indium sulfate according to claim 1, characterized in that: The concentration of the sulfuric acid solution is 10-200 g / L.

4. The method for preparing high-purity anhydrous indium sulfate according to claim 1, characterized in that: The solid-liquid ratio of the indium bar to the sulfuric acid solution is 1 g: (4-6) mL.

5. The method for preparing high-purity anhydrous indium sulfate according to claim 1, characterized in that: The temperature of the heating reaction is 75-85°C.

6. The method for preparing high-purity anhydrous indium sulfate according to claim 1, characterized in that: The temperature of evaporation concentration in step (2) and step (3) is 90-100°C.

7. The method for preparing high-purity anhydrous indium sulfate according to claim 1, characterized in that: The temperature of the evaporation, concentration and crystallization is 90-100° C. and the time is 6-12 hours.

8. The method for preparing high-purity anhydrous indium sulfate according to claim 1, characterized in that: The detergent comprises at least one of anhydrous acetic acid, anhydrous formic acid and hydrogen cyanide.

9. The method for preparing high-purity anhydrous indium sulfate according to claim 1, characterized in that: The nitrogen gas introduction rate is 10-15 L / min.

10. The method for preparing high-purity anhydrous indium sulfate according to claim 1, characterized in that: The temperature of the thermal decomposition is 300-500° C., and the time of the thermal decomposition is 10-15 hours.

Citation Information

Patent Citations

  • Method and device for preparing indium sulfate

    CN103880065A